THE INFLUENCE OF COMPETENCE JOB STRESS AND WORKLOAD THROUGH JOB SATISFACTION ON EMPLOYEE PERFORMANCE (Case Study at PT. Serasi Shipping Indonesia, East Kalimantan Province) - Ruliana, Titin (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: The purpose of this research is to determine and analyze the influence of competence, work stress, and workload on employee performance through employee job satisfaction as a moderating variable. Design/methodology/approach: quantitative research with a correlational approach. The population and sample of this research are all employees of pt. Serasi shipping Indonesia, east Kalimantan province, totaling 41 people. Data analysis uses partial least squares. Findings: competency research results, work stress, and workload have a significant effect on employee job satisfaction. Competence and work stress do not have a significant effect on employee performance. Workload and job satisfaction have a significant effect on employee performance. Competence, work stress, and workload have a significant indirect effect on employee performance with job satisfaction as a moderating variable pt. Serasi shipping indonesia, east kalimantan province.